2021
DOI: 10.1016/j.jtocrr.2020.100115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Methods for Defining Hyperprogressive Disease in NSCLC

Abstract: Introduction: Hyperprogressive disease (HPD) as a consequence of immune checkpoint inhibitors in NSCLC has been reported in multiple studies. However, inconsistent results in incidence and survival outcomes within studies, together with different assessment methods, have led to increasing controversy regarding the concept of HPD.Methods: Consecutive patients treated with nivolumab (N ¼ 42) or docetaxel (N ¼ 37) were evaluated. HPD was quantified by applying three different methods (tumor growth rate [TGR], tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Incidences of HPD in NSCLC patients treated with ICI monotherapy have varied, increasing in the order of ΔTGR, TGR ratio, and TGK ratio as follows 5.1% (n=12), 15.6% (n=37), and 18.1% (n=43) in one study (14), and 5.7% (n=8), 11.3% (n=16), and 17.0% (n=24) in the other study (7). However, two studies reported a similar proportion of NSCLC patients with HPD based on TGR ratio and TGK ratio (TGR ratio vs. TGK ratio: 20.5% (n=54) vs 20.4% (n=55), and 16.7% (n=7) vs. 16.7% (n=7), respectively) (21, 22). Notably, the definitions of HPD varied across these studies.…”
Section: Discussionmentioning
confidence: 93%
“…Incidences of HPD in NSCLC patients treated with ICI monotherapy have varied, increasing in the order of ΔTGR, TGR ratio, and TGK ratio as follows 5.1% (n=12), 15.6% (n=37), and 18.1% (n=43) in one study (14), and 5.7% (n=8), 11.3% (n=16), and 17.0% (n=24) in the other study (7). However, two studies reported a similar proportion of NSCLC patients with HPD based on TGR ratio and TGK ratio (TGR ratio vs. TGK ratio: 20.5% (n=54) vs 20.4% (n=55), and 16.7% (n=7) vs. 16.7% (n=7), respectively) (21, 22). Notably, the definitions of HPD varied across these studies.…”
Section: Discussionmentioning
confidence: 93%
“…Illustrated by Figure 8 , a significant discrepancy was found among the five subgroups ( P = .02). The pooled incidence of HPD was 16.2% in patients suffering from gastrointestinal (GI) tract cancer ( n = 5, 95% CI, 10.4%–24.1%) ( 33 , 45 , 56 , 57 , 60 ); 14.4% in patients with NSCLC ( n = 14, 95% CI, 12.2%–17.0%) ( 13 , 16 , 17 , 21 , 29 , 34 , 42 44 , 51 , 54 , 59 , 62 , 63 ), 9.9% in patients with melanoma ( n = 3, 95% CI, 1.6%–43.4%) ( 35 , 36 , 53 ); 10.8% in patients with HCC ( n = 4, 95% CI, 8.4%–13.8%) ( 14 , 39 , 40 , 61 ); 18.06% in patients with HNC ( n = 6, 95% CI, 15.0%–21.6%) ( 15 , 37 , 38 , 48 , 49 , 52 ). Significant differences were found between these five tumor types (Q = 11.16, P = .0248), indicating that tumor type is a source of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…TGK is also a common approach for HPD evaluation. To further reassure clinicians of the HPD diagnosis, some studies calculate both TGR and TGK to verify the final evaluation ( 29 , 34 , 39 , 40 ). Other criteria are also used to describe the HPD phenomenon, including “more than 40% or 50% increment of total tumor burden,” “ECOG PS exceeding 2 during anti-tumor treatment,” and “more than two new lesions exist in previously involved organ or new organs.” However, these criteria are not in consensus for the oncological community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different definitions may result in a wide variation in HPD incidences. ICI-induced HPD remains controversial because of a lack of consensual definition, and HPD definitions are very heterogeneous in terms of incidence rate and clinical impact (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%